Forces for change in social impact assessment. Issue 4 (3rd July 2020) - Parsons, Richard
ABSTRACT: Social impact assessment (SIA) is experiencing both evolutionary and revolutionary forces for change. Using the example of New South Wales, Australia, forces for change include community pressure and shifting expectations, industry desire for clarity and certainty, departmental leadership, a collaborative approach to policy development, and perceived legitimacy of the guideline itself. Inhibiting these forces are general resistance to change, a concern around costs of good SIA, unfamiliarity with social sciences, and insufficient practitioner capacity. The recent Rocky Hill judgement, which highlights concepts such as community cohesion, sense of place, and distributive equity, may accelerate change. However, there is also a need to build capacity among SIA practitioners, and afford sufficient time and budget to meet the standard of leading-practice guidelines. At the same time, unfolding trends such as the climate change and extinction crises, the gendered nature of development, ever-widening inequalities, and 'post-truth' discourses may catalyse more revolutionary change in SIA practice – changes that paradoxically may enable SIA to reclaim its social-science principles and the overarching goal of sustainable social development.